Finding the vulnerable among China's elderly: identifying measures for effective policy targeting. Issue 3 (27th May 2019) - Kong, Tao; Yang, Po
ABSTRACT: Facing a rapidly aging population, China has recently started to formulate and implement policies with the aim to provide old-age care. While well-developed old-age care policies commonly include a built-in component that assesses eligibility based on vulnerability, no such process is established in the context of China. Here, based on data from the China Health and Retirement Longitudinal Study collected in both 2011 and 2013, we (a) developed a simple and effective strategy for identifying vulnerable Chinese elderly, which can serve as a basis for policy targeting, and (b) improved the policy relevance and targeting efficiency of this vulnerability measure by including additional health indicators. Our vulnerability measures identify 35% to 46% of Chinese elderly as vulnerable, covering up to 67% of elderly at high risk of death or functional decline. They can serve as an initial screening step for more comprehensive geriatric assessments and enable policy makers to effectively target vulnerable elderly persons in China.